K. KARPIŃSKA-SZAJ, A. LEWANDOWSKA, A. SOPATA, B. WOJCIECHOWSKA, Reformulation in foreign language learning, Poznań: Wydawnictwo Naukowe UAM, 2019 - Seretny, Anna (Neofilolog, 2021)
Recenzja: K. KARPIŃSKA-SZAJ, A. LEWANDOWSKA, A. SOPATA, B. WOJCIECHOWSKA, Reformulation in foreign language learning, Poznań: Wydawnictwo Naukowe UAM, 2019.